Behavioral Intention Constituent Analysis of QRIS Digital Payment Tools in MSMEs in Pematangsiantar City - Novita Butarbutar; Ernest Grace; Loist Abdi Putra; Christine Loist; Acai Sudirman (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
The main goal of this study is to examine the variables that affect MSMEs in Pematangsiantar City s behavioral intention to utilize the QRIS digital payment instrument. A causal quantitative research strategy was used in this study. 250 SMEs served as the study s sample population. Partial Least Squares is the technique used for data analysis (PLS). The statistical program Smartpls 3.0 is used by the data analysis test tool. The results of this study conclude performance expectancy and social influence have a positive but not significant effect on behavioral intention. This study also concludes that effort expectancy, hedonic motivation, trust, lifestyle compatibility, and habit positively and significantly affect behavioral intention. The managerial implications of this research mention that habit and trust are the main factors for MSME actors to adopt payment systems with QRIS. This of course can be used as a recommendation for QRIS providers to improve the performance of several QRIS platforms in the form of increasing security features, so that this will foster a sense of comfort and high trust from users to use and recommend QRIS to others.